Methodology of the integrated analysis of company‘s financial status and its performance results - Mackevičius, Jonas; Valkauskas, Romualdas (Business: Theory and Practice, 2010)
Information about company‘s financial status and its performance results is very important for the objective evaluation of company‘s position in the market and competitive possibilities in the future. Such information is provided in the financial statement. It is important to apply and investigate this information properly. The methodology of company‘s financial status and performance results integrated analysis is recommended in this article. This methodology consists of these three elements: 1) research of absolute financial indicators variation; 2) calculation and estimation of relative financial indicators (these are the elements of a traditional finance analysis);  3) standardization and analysis of indicators. Applying this methodology it is enough to use 8–10 indicators to estimate financial status and performance results of small and medium entities and 15–20 indicators to estimate financial status and performance results of large entities. The methodology of company‘s financial status and performance results integrated analysis allows calculating variations of absolute financial indicators and to reveal the grounds of these variations and to suggest the decisions to improve the current situation for the management of the company. The third element of this analysis - standardization and analysis of indicators, allows revealing the aspects of commercial – industrial activities. Application of all three elements of integrated analysis will help company‘s management to evaluate current financial status of the company and its performance results and to make proper management decisions that will guarantee the succession of company‘s activity and good financial results in the future.Article in Lithuanian.Integruota įmonės finansinės būklės ir veiklos rezultatų analizės metodikaSantrauka. Siekiant  objektyviai  įvertinti  dabartinę  įmonės  vietą  rinkoje  ir  jos  konkurencines  galimybes  ateityje,  labai  svarbi informacija  apie  finansinę  įmonės  būklę  ir  veiklos  rezultatus.  Tokią  informaciją  suteikia  finansinė  atskaitomybė.  Svarbu  tinkamai panaudoti šią informaciją, mokėti ją ištirti. Straipsnyje rekomenduojama integruota finansinės įmonių būklės ir veiklos rezultatų analizės metodika. Ją sudaro trys elementai: 1) absoliučiųjų finansinių rodiklių pokyčių tyrimas; 2) santykinių finan-sinių rodiklių skaičiavimas ir vertinimas (tai tradicinės finansinių rodiklių analizės elementai); 3) rodiklių standartizavimas ir jų analizė. Taikant šią metodiką finansinės mažų ir vidutinių įmonių būklės bei veiklos rezultatams įvertinti pakanka 8−10, o didelių įmonių – 15–20 rodiklių. Integruota finansinės įmonių būklės bei veiklos rezultatų analizės metodika leidžia apskaičiuoti absoliučiųjų rodiklių pokyčius ir atskleisti jų priežastis, o apskaičiavus santykinius rodiklius nustatyti jų gerą ar blogą „būseną“ (skaitinę reikšmę), pasiūlyti vadovybei, kokius derėtų priimti sprendimus padėčiai ištaisyti. Trečiojo analizės elemento – rodiklių standartizavimo procedūros naudojimas padeda atskleisti komercinės ir ūkinės veiklos puses, kurių gerinimas padeda pasiekti optimalius finansinės būklės ir veiklos rezultatus. Visi trys integruotos analizės elementai padės įmonės vadovybei objektyviai įvertinti dabartinę finansinę įmonės būklę ir veiklos rezultatus, priimti teisingus valdymo sprendimus, užtikrinančius įmonės konkurencingumą rinkoje, veiklos tęstinumą ir gerus finansinius rodiklius ateityje.Reikšminiai žodžiai: integruota finansinės būklės ir veiklos rezultatų analizė, absoliutieji finansiniai rodikliai, santykiniai finansiniai rodikliai, duomenų standartizavimas.